THE POLICIES OF PUBLIC OUTLAY AND ITS IMPACT OF DEFICIT ON IRAQ'S GENERAL BUDGET (ANALYTICAL STUDY FOR THE PERIOD 2004-2020) - Arshed Makki Rashid (Scholars Digest Publishing, 2023)
The Iraqi economy suffers from clear instability in its economic policies in light of the worsening public budget deficit as a result of increased government spending on the one hand and the fluctuation of public revenues, rising and falling on the other hand, as the decline in oil prices since mid-2014 resulted in a clear deficit in the general budget. For the state before oil prices rose, and then oil prices fell again in the year (2020) after the spread of the (covid-19) epidemic and its repercussions on the global economy in general and Iraq in particular, which requires research into approved mechanisms to treat this deficit and relieve pressure on the state’s general budget This study concluded that the state should resort to the work of the Revenue Control Fund, rationalize public expenditures, and work hard in order to diversify the sources of public revenues in Iraq.
Keywords: Iraq general budget , public revenues , economic policies , clear instability , revenue control fond , oil price.